Recent Changes in Drug Abuse Scenario: The Novel Psychoactive Substances (NPS) Phenomenon - Fabrizio Schifano (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In parallel with a decrease/stabilization in the use of internationally controlled drugs, the market of novel psychoactive substances (NPS) continues increasing, year after year, with the Internet playing a pivotal role in contributing to this complex scenario. At times, although misleading, the terms 'legal highs' or 'research chemicals' have been used to describe these molecules. Overall, about 5% of 19-24-year-old European people have already experimented with them, because both NPS' intense psychoactive effects and their virtual non-detectability in routine drug screenings. Although 'novel' typically refers to molecules that have recently become a reason of current/potential public health concern, at times, the NPS scenario may indeed focus on pharmaceutical molecules. These may have either not entered the market, or are currently prescribed, with their potential for misuse resulting from the relating high dosages/idiosyncratic ways of self-administration. A concurrent use of a range of different NPS, and/or medications, is frequently being reported and this may be a reason of further clinical complications. Given their complex pharmacodynamics, there are increasing levels of concern about the onset of acute/chronic psychopathological associated with NPS intake. This Special Issue aims at providing an overview of a range of NPS-related issues, e.g., preclinical, epidemiological, and clinical pharmacological; the medical and psychopathological consequences associated with their intake; and, finally, the analytical chemistry and forensic analysis challenges associated with the NPS phenomenon.